Sebuah Pengembangan Media Pembelajaran PowerPoint-iSpring pada materi kimia hijau dan pemanasan global fase E SMA/MA - Diastuti, Yuli; Guspatni (Postgraduate, University of Mataram, 2024)
PowerPoint-iSpring media supports the learning process where it can display images, videos, animations, text, and others that can increase student activity and learning outcomes. The aim of this research is to produce valid PowerPoint-iSpring learning media on green chemistry and global warming phase E SMA/MA. The type of research used is Educational Design Research with the Plomp model. The validity test was carried out by four chemistry lecturers at FMIPA UNP and two teachers at SMAN 14 Padang by filling out a validation questionnaire. One-to-one evaluation was carried out by three students with different levels of ability. Validation data was analyzed using the Aiken' V index. The results of the content validity test research obtained a value of 0.92 for green chemistry and global warming in the valid category. The construct validity test obtained a value of 0.93 in the valid category and the technical quality validity test obtained a value of 0.93 in the valid category. The average validity test result of PowerPoint-iSpring learning media on green chemistry and global warming is 0.92 in the valid category. The results of the one-to-one evaluation received a good response from students.